THE EXISTENCE OF THE STUDENT ACTIVITIES UNIT (UKM) CENTER FOR AL-QUR'AN DEVELOPMENT STUDIES (PUSPA) IN HIGHER EDUCATION - Daniah (MEDIA DAN STRATEGI PEMBELAJARAN, 2024)
This research is motivated by the achievements of Mataram State Islamic University (UIN) students in the field of the art of Al-Qur'an recitations which were achieved at the Musabaqah Tilawatil Qur'an (MTQ) event at various levels. This research is descriptive qualitative research and field research taking place at the Student Activity Unit (UKM) of the Al-Qur'a Development Study Center (PUSPA) of Mataram State Islamic University (UIN), Mataram City, West Nusa Tenggara Province. Data collection techniques use observation, interviews, documentation, and field notes. Data analysis techniques use data condensation, data presentation, and conclusion. The results of this research indicate that the existence of the Student Activity Unit (UKM) Center for Al-Qur'an Development Studies (PUSPA) at the Mataram State Islamic University (UIN) can be a forum for students to explore and develop skills in the art of reciting the Al-Qur'an. In improving the art of reciting the Al-Qur'an, the existence of the Student Activity Unit (UKM) Center for Al-Qur'an Development Studies (PUSPA) can actualize student abilities through training in the art of reciting the Al-Qur'an which has been designed with an excellent strategy by the department the art of reciting the Qur'an which includes planning, implementation, and evaluation. Apart from that, the administrators in the field of recitation arts create strategies in the form of indicators that must be mastered by students as stages of achievement in improving the art of reciting the Qur'an, including fasohah (reading fluency), mastery of naghom (songs), understanding related to the science of Tajwid, supportive voice, and breath. Then, in improving the art of reciting the Qur'an, there are supporting and inhibiting factors, both from within the student and from outside the student.